Class, states and international relations : a critical appraisal of Robert Cox and neo-Gramscian theory - Budd, Adrian, 1961- (Milton Park, Abingdon, Oxon : Routledge, 2013)
"This book provides both an outline and a critique of neo-Gramscian international relations theory, from a Marxist perspective"--
pt. 1. Robert Cox and neo-Gramscian theory -- pt. 2. Critique.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cox, Robert W., -- 1926-; Gramsci, Antonio, -- 1891-1937.; International relations -- Philosophy; International relations -- Social aspects; International organization; Electronic books